Environmental Information System in India - Singh, Harjit (DESIDOC Journal of Library & Information Technology, 2003)
ENVIS is a decentralised network information system comprising 24 subject specific centres in the Ministry of Environment and Forests, Govt of India. This article outlines the objectives of Environmental Information System (ENVIS). It describes the responsibilities and activities of ENVlS Focal Point and Centres. The author concludes with the futuristic views of ENVIS. http://dx.doi.org/10.14429/dbit.19.2.3467